(untitled) (Journal of the College of Basic Education, 2022)
The combustion efficiency in most internal combustion engines are not up to 90% so the part of the fuel you will does not burn and come out with the exhaust gases, leading to increasing the fuel consumption and increasing emissions to the atmosphere. Therefore has been made several attempts to increase the combustion efficiency and reduce emissions. So which used a new way to reduce the fuel consumption by using magnetic field to complete the combustion, This leading to obtain maximum thermal efficiency and the reduction the emissions by subject of fuel by force magnetic flux of the magnet is installed at the entrance of the of fuel feeding , leading more efficient combustion. .The result which is obtained reducing the fuel consumption (L/h) up to (5.3%) . The exhaust gas emissions also showed a reduction nearly by (7.038 %) of CO, (0.314 %) of CO2 and (10.126%) of HC.